Kebutuhan Peningkatan Kualitas Layanan Angkutan Umum Perdesaan Studi Kasus Trayek 061 Cilimus-Mandirancan Kabupaten Kuningan Jawa Barat - Adinda Sekar Tanjung; Puspita Dirgahayani (Journal of Science and Applicative Technology, 2021)
Trend of public transport service in rural area is decreasing in terms of the number of operational route and the performance. However, there are people who cannot access private vehicles and depend on rural transport services including the elderly, people with disabilities, women, and students. The existence of this rural transportation indirectly improves the quality of life of the community by providing easier access to better economic, health and educational facilities than in the areas where they live. Responding to these conditions, the aim of this study is to analyze rural transit service needs to accommodate passengers trip. Case study of this research is rural public transport on route 061 Cilimus-Mandirancan in Kuningan Regency. This study used quantitative method with descrptive and comparative analysis. The result show that public transport needs improvement in such performance parameter like route, schedule, load factor, waiting time, baggage space, vehicle operating cost, and institutional. Improving the quality and innovation of rural public transport services can be realized if there is intervention from the government and other related parties in the management and operational costs of rural public transport vehicles.